A Measure of Fairness: The Economics of Living Wages and Minimum Wages in the United States - Osberg, Lars (Labour / Le Travail, 2009)
This article reviews the book, "A Measure of Fairness," by Robert Pollin, Mark Brenner and Jeannette Wicks-Lim.
Keywords: BOOKS -- Reviews; BRENNER, Mark; Book reviews; Business And Economics--Labor And Industrial Relations; History--History of North And South America; LUCE, Stephanie; Labor economics; MEASURE of Fairness: The Economics of Living Wages & Minimum Wages in the United States, A (Book); Minimum wage; Nonfiction; POLLIN, Robert; United States; WICKS-Lim, Jeannette; Wage price policy; Wages